Autonomic Nervous System and Cognitive Impairment in Older Patients: Evidence From Long-Term Heart Rate Variability in Real-Life Setting - Dalise, Anna Maria; Prestano, Raffaele; Fasano, Renata; Gambardella, Antonio; Barbieri, Michelangela; Rizzo, Maria Rosaria (Frontiers in Aging Neuroscience, 2020)
ABSTRACT BACKGROUND In geriatric age, cognitive impairment and cardiovascular disorders are frequent comorbidities. Age-related anatomical and functional cardiac changes, including the autonomic system, could interfere with the control of different cognitive domains. Therefore, we assess the relationship between long-term heart rate variability (HRV), as measure of autonomic nervous system (ANS) functioning, and cognitive performances, in elderly patients representative of the outpatients in a real-life setting. METHODS Of 155 elderly outpatients (aged >65) screened, 117 enrolled patients underwent anthropometric evaluation, cardiac assessment by 12-leads electrocardiogram, 24-hour ECG recording and blood pressure (BP) measurement as well as global cognitive evaluation by a standardized multidimensional assessment, including Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment test (MoCA). HRV analysis was performed on 24-hour ECG recordings focusing on Time-domain indices (SDNN, SDANN and RMSSD) and on Frequency-domain measurements (HR, LF, HF, LF/HF). Multivariate linear analysis was used to explore the influence of the HRV significant variables on MMSE and MoCA test values. RESULTS MMSE and MoCA scores were both significantly and positively correlated with sympathetic system parameters (SDNN, SDANN, LF and LF/HF ratio) but not with parasympathetic system (rMSSD and HF) parameters. Multivariate analysis confirms this relationship. CONCLUSIONS Our results show that, in a representative real-life community elderly population, increased sympathetic activity, but not decreased vagal activity is associated with better cognitive performances. These results support the sympathetic autonomic function, in that the relationship between better cognitive performances and moderate prevalence of autonomic function appears dependent on long-term changes in heart rate, mediated by sympathetic activation.